Estimating epiphytic lichen richness by single families in Mediterranean forests - Aragón, Gregorio; Belinchón, Rocío; Martínez, Isabel; Prieto, Maria (Forest Ecology and Management, 2013)
The current trend of declining epiphytic richness caused by human activities (forest fragmentation, log- ging, agriculture, and livestock grazing) and the greater efforts required to sample and identify the most inconspicuous species have necessitated the use of indicators of the species richness. In this study, we examined the potential of predicting epiphytic lichen richness based on the richness of a single taxon (fam- ily) of the most conspicuous lichens (macrolichens) in Mediterranean woodlands. Since our working hypothesis is that the richness of some conspicuous elements is tightly connected with the total richness, we expect this connection is maintained even after composition shifts (for instance composition changes between coniferous and oak forests). In order to control the large set of confounding factors at macro- and microclimate scales our present study was conducted in 504 forest stands, which represented awide range of Mediterranean climates, management intensity levels, canopy cover types, and tree sizes. The presence/ absence of epiphytic lichens were determined in 7560 trees, which were dominated by coniferous (Pinus nigra and P. sylvestris) and oak (Quercus ilex ssp. ballota, Q. faginea, and Q. pyrenaica) species. In oak forests, the increased richness of Collemataceae and the complex known as ‘‘rest of Peltigerales’’ was followed by an increase in the overall epiphytic richness, whereas there was a strong positive correlation between Par- meliaceae and total epiphytic richness in coniferous forests. In both cases, the richness of these predictors increased in well-preserved forest stands with dense canopies. Thus, we propose the potential use of Par- meliaceae (for coniferous forests) and the Collemataceae and the ‘‘rest of Peltigerales’’ (for oak forests) as indicators in the Mediterranean region because they have a cosmopolitan distribution, grow in a wide range of environmental conditions, and are correlated with changes in the epiphytic richness caused by for- est disturbances. ?
From Duplicate 2 ( Estimating epiphytic lichen richness by single families in Mediterranean forests - Aragón, Gregorio; Belinchón, Rocío; Martínez, Isabel; Prieto, Maria )From Duplicate 2 ( Estimating epiphytic lichen richness by single families in Mediterranean forests - Aragón, Gregorio; Belinchón, Rocío; Martínez, Isabel; Prieto, Maria )
Keywords: epiphytic lichens; Forest structure; Indicator species; Mediterranean; Species richness

Lichen functional groups as ecological indicators of the effects of land-use in Mediterranean ecosystems - Pinho, P; Bergamini, A; Carvalho, P; Branquinho, C; Stofer, S; Scheidegger, C; Máguas, C (Ecological Indicators, 2012)
The effects of land-use on species and communities are usually studied by considering high-intensity land-use gradients. However, in many Mediterranean Europe areas, the traditional land-use regime is of low-intensity, including low-impactforestry practices and extensive livestock pasture. This low-intensity land-use is associated with ‘High Nature Value Farmlands’, which occupymore than 50% oftotal farmland area in Mediterranean areas. The objective of this work was to determine the effect of traditional lowintensity land-use on epiphytic lichen communities in Mediterranean cork-oak woodlands. We intend to investigate the value of lichen communities as early indicators of the effects of land-use changes. For that, lichens were sampled along a gradient of low-intensity land-use that included forestry and pasture activities. As lichen diversity variables we considered: (i) total species richness, (ii) total species frequency (LDV), and (iii) richness and frequency of functional groups dividing species according to their eutrophication-tolerance. We found an increase of total species richness with an increase of land-use intensity which is opposite to expectations and which was shown for ﬁrst time in lichens. The increase in total species richness was due to an increase of the number of eutrophication tolerant species accompanied by the maintenance of the sensitive one when we analyzed the lichen-data at the functional response group level. These results ﬁt with the intermediate disturbance hypothesis that predicts higher diversity under an intermediate disturbance due to the coexistence of species with contrasting ecological requirements. Traditionally managed cork-oak woodlands with low-intensity land-use can thus support a high diversity of lichen species. An important outcome was that we conﬁrmed the importance of using ecological indicators based on functional-groups for monitoring changes in ecosystems and, since lichens responded to low levels of land-use intensity, we have also shown the possibility of using lichens as early indicators of the impacts of low intensity land-use.
Keywords: Ecological indicators; epiphytic lichens; livestock; management; Nitrophytic; Oligotrophic; Quercus suber

Epiphytic lichens and bryophytes of forest ecosystems in Tuscany (Central Italy) - Loppi, Stefano; Bonini, Ilaria; de Dominicis, Vincenzo (Cryptogamie Mycologie, 1999)
The distribution of epiphytic bryophytes and lichens on three species of trees (Quercus ilex, Quercus cerris and Fagus sylvatica, representing the forest ecosystems of central Italy at low, medium and high elevations, respectively) was examined with respect to host specificity and habitat differences. Although most species were host-specific, the results suggested that habitat characteristics are more important than phorophyte properties in determining the distribution of lichens and bryophytes. Factors affecting the diversity of the epiphytic flora were different for lichens and bryophytes. In the case of lichens, climatic parameters and forest monospecificity were important factors, whereas tree cover (i.e. shade) and to a certain extent the number of available trees seemed more important for bryophytes.
Keywords: distribution (voyant); epiphytic bryophytes; epiphytic lichens; forest ecosystems; Host specificity

Epiphytic lichens and bryophytes of forest ecosystems in Tuscany (Central Italy) - Loppi, Stefano; Bonini, Ilaria; de Dominicis, Vincenzo (Cryptogamie Mycologie, 1999)
The distribution of epiphytic bryophytes and lichens on three species of trees (Quercus ilex, Quercus cerris and Fagus sylvatica, representing the forest ecosystems of central Italy at low, medium and high elevations, respectively) was examined with respect to host specificity and habitat differences. Although most species were host-specific, the results suggested that habitat characteristics are more important than phorophyte properties in determining the distribution of lichens and bryophytes. Factors affecting the diversity of the epiphytic flora were different for lichens and bryophytes. In the case of lichens, climatic parameters and forest monospecificity were important factors, whereas tree cover (i.e. shade) and to a certain extent the number of available trees seemed more important for bryophytes.
Keywords: distribution (voyant); epiphytic bryophytes; epiphytic lichens; forest ecosystems; Host specificity

The Sines industrial complex monitoring programme: a preliminary report - Jones, M P; Catarino, F M (Environmental Monitoring …, 1981)
It is anticipated that the establishment of the industrial complex at Sines, Alentejo, Portugal, will have some impact on the environment. Details of the methods used in the monitoring programme are provided. Records of the epiphytic lichen vegetation in permanent quadrats have been made and changes shown in selected sites over a three year period are discussed. Material has been collected for analysis for heavy metals and the results discussed. There is considerable variation in replicates and in interspecies values. The problem of age and bio-accumulation is mentioned. Scanning electron microscopy has shown the accumulation of particulates, as yet unidentified, the quantity varying with increase in age and surface texture. A broadly based study of the local epiphytic flora is being carried out to record the present day diversity. There appears, as yet, to be no detectable influence of the industrial complex on the epiphytic flora of the permanent quadrats.
Keywords: bio-accumulation; epiphytic lichens; Monitoring programmes (voyant); Sines industrial complex